Les pratiques préconisées en formation pour faire la classe interviennent-elles dans les planifications des futurs enseignants de français ? - Barbier, Elise; Colognesi, Stéphane (Canadian Journal of Education/Revue canadienne de l'éducation, 2023)
Planning teaching/learning activities is one of the essential tasks of “doing the classroom”. In order to carry out this task, teacher education students are expected to use the practices proposed in training and recommended by research. We sought to identify the extent to which students mobilize these practices in their planning of teaching/learning activities. To do this, all the plans made by 18 future French teachers for their last four-week placement were collected. The results of the content analysis show the importance of practices such as the management of content to be taught, the communication of objectives, the use of existing teaching resources, the management of difficulties and the links between subjects. Furthermore, it appears that the future teachers participating in our study anticipate little, if at all, their feedback, the time of involvement of students in the evaluation process and metacognition. These observations are challenges for initial teacher education.